An alien among aliens: Translating multicultural identities in Singapore’s contemporary theatre - Bei Hu (JoSTrans: The Journal of Specialised Translation)
This article explores the conﬂated roles of translator and playwright embodied by Kuo Pao Kun (1939-2002), a doyen figure acclaimed as the embodiment of Singapore’s contemporary theatre. As a Singaporean arts activist born in China, Kuo reformulated the state identity of Singapore through his self-translated play Descendants of the eunuch admiral (1995a), which examines his perceptions regarding the perils of a homogenised national theatrical realm and the tensions emerging from modernisation — an intriguing standpoint for an ethnically Chinese art activist. This lyrical episodic play unfurls the representation of the self-discovery of Zheng He, the Chinese admiral and court eunuch during the Ming Dynasty (1368–1644). Stratified into prose and verse, it weaves tales and metaphors that highlight the dissolution of cultural identities, and the societal challenges faced due to emasculation. This study focuses on Kuo’s translator intervention in the bilingual versions of the play, one staged in English in June 1995 and the other in Mandarin Chinese in August 1995. It reveals Kuo’s proposition of multiculturalism as a counternarrative to the official discourse of multiracialism propagated by the authorities, uncovering how playwrights represent as translation agents within multilingual narratives.